Pengaruh Kualitas Produk, Harga, Dan Influencer Marketing Terhadap Keputusan Pembelian Skincare Avoskin : (Studi Kasus pada Konsumen Sociolla Summarecon Mall Bekasi) - Fitriyah, Khansa Aufa; Saing, Bungaran; Sudiantini, Dian (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The significant difference in sales between Avoskin skincare products and competing products indicates a challenge for Avoskin to strengthen its consumer appeal. The purpose of this study is to determine the influence of product quality, price, and influencer marketing on consumer purchasing decisions. The research employed a quantitative method with a survey approach. Data were collected through questionnaires distributed to 102 respondents who had previously purchased Avoskin skincare products at the specified location. The data were analyzed using multiple linear regression with the assistance of SPSS version 26 to examine both partial and simultaneous relationships between variables. The results indicate that product quality (t-value = 5.289, sig. = 0.000), price (t-value = 2.236, sig. = 0.028), and influencer marketing (t-value = 7.106, sig. = 0.000) each have a positive and significant effect on purchase decisions. Furthermore, these three variables simultaneously have a significant influence on consumer purchasing decisions (f-value = 35.673, sig. = 0.000). The coefficient of determination (R²) indicates that 50.7% of the variation in purchasing decisions can be explained by the three independent variables.